INTRODUKSI TEKNOLOGI VERMIKOMPOSTING DALAM UPAYA PENGELOLAAN LIMBAH PETERNAKAN DI DESA SRIKUNCORO, BENGKULU TENGAH - Anandyawati, Anandyawati; Nur Dita Nugroho, Mohammad; Muktamar, Zainal (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
The great potential of Srikuncoro Village is from the agricultural and livestock sectors. The livestock sector, in addition to producing main products such as eggs, meat and milk, also produces by-products that have not been utilized properly. The product is livestock manure which if not managed properly will become livestock waste. One of the simple, easy, inexpensive and adaptive technologies is waste management through vermicomposting technology, which is a composting process carried out with the help of worms. The implementation of community service activities in Srikuncoro village is carried out through socialization and the practice of vermicomposting technology using Lumbricus rubellus worms. The activity was carried out from July to November 2021 and was attended by 20 members of the Lotus Farmer Group Association, Srikuncoro Village. This service activity resulted in several achievements, including: 1. Increased knowledge of the Srikuncoro village community (represented by members of the farmer group association) in livestock waste management through vermicomposting technology; 2. Increased knowledge about the cultivation of Lumbricus rubellus worms; 3. The emergence of public interest in making vermicomposting a side job (besides raising livestock) by building vermicomposting with the direction and guidance of a service team; and 4. The successful transfer of knowledge on vermicomposting technology from the service team to the community.